Biopreservative Action of Bacteriocin from Pediococcus pentosaceus on the Microbial Load of Apple Juice - Majumder, Riyanka; Aditya, Ankita; Dey, Sreyosi; Siddique, Jannatul Firdous; Anbalagan, Nivetha; Devi, Subathra; Vaithilingam, Mohanasrinivasan (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: The aim of the study is to explore the bio preservative role of Pediococcus pentosaceus. Background: Bacteriocins are proteinaceous or peptidic in nature produced by lactic acid bacteria and generally recognized as safe (GRAS). It ranges from 2 to 200kDa in molecular weight. It inhibits the growth of similar or closely related bacterial strains. Materials and Methods: In this experiment, “Appam batter” has been taken as our sample, collected from Vellore city. The sample was fermented for seven and fourteen days simultaneously from which 1mL of the samples were taken and inoculated in 100mL of production media consist of 3% skim milk. The bacteria were allowed to grow for 24 hrs and serially diluted and spread plate was done on MRS agar plate. Seventeen bacterial strains were isolated. The preliminary assays were carried out to identify the bacteria as Lactobacillus species, such as Gram staining and catalase. All the strains were screened for bacteriocin by agar well diffusion assay. The strains which showed zone of inhibition was further subjected to antibacterial activity. Results: The isolated strains were found to show a clear zone of inhibition against Listeria monocytogenes MTCC 5260 used as the indicator strain. Further the isolated strains were tested for antimicrobial activity against certain food borne pathogens which includes Staphylococcus aureus MTCC 5257, Salmonella typhi MTCC2501, Escherichia coli MTCC 2089 and Pseudomonas aeruginosa MTCC 2242. The isolated strain VITAB01 showed a broad spectrum activity against all the pathogens with a highest zone of inhibition of 13mm, 12800(AU/mg) and thus subjected to 16srRNA molecular level analysis and found out to be Pediococcus pentosaceus MH134499. The isolate upon characterization showed to be heat stable at 60°C and optimum pH 6. On purification it has a specific activity of 325.20(AU/ mg) with a final yield of 3.12. The molecular weight of the bacteriocin was found to be 17kDa. Conclusion: The supernatant was mixed with apple juice and checked for its bio preservative effect. Decrease in colonies was found to be 26.82%.
Keywords: Appam batter; Lactic Acid Bacteria; Purification; Bacteriocin; Apple juice; Preservative